2022
DOI: 10.23960/jsl.v10i1.525
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Institutional Conditions in Social Forestry Program: Case Study of Forest Village Community Institution (LMDH) Sumber Makmur, Forest Management Unit (KPH) Malang

Abstract: Changes in the Social Forestry or Perhutanan Sosial (PS) scheme have been made by the Ministry of Environment and Forestry of the Republic of Indonesia, particularly in the state-owned forestry enterprise (Perhutani) working area. A forestry partnership is one of the schemes being developed to replace the previous scheme, Community Forest Management (PHBM). However, increased PS area permits are not always accompanied by increased farmer trust and understanding of the program. This study aimed to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…They highlighted the importance of considering outcomes related to environmental sustainability and climate resilience when studying digital advisory and extension services for farmers. (Ramadhan, Syah, and Waskitho 2022) Explored farmer groups' effectiveness and institutional condition under the Social Forestry scheme in Indonesia. They found that increased permits only sometimes led to increased farmer trust and understanding of the program, emphasizing the need for monitoring and institutional development.…”
Section: Previous Researchmentioning
confidence: 99%
“…They highlighted the importance of considering outcomes related to environmental sustainability and climate resilience when studying digital advisory and extension services for farmers. (Ramadhan, Syah, and Waskitho 2022) Explored farmer groups' effectiveness and institutional condition under the Social Forestry scheme in Indonesia. They found that increased permits only sometimes led to increased farmer trust and understanding of the program, emphasizing the need for monitoring and institutional development.…”
Section: Previous Researchmentioning
confidence: 99%
“…It might be due to the varying influence of the number of family members on the family's economy, affecting food security. The more family members there are, the more mouths there are to feed (Ramadhan et al 2022;Ruhyana et al 2020;Santoso et al 2023). However, if multiple family members contribute to the household's income and not just the head of the family, it can help improve the family's food security since they are economically supported by more than one person (Sulistyo et al 2022;Wijaya et al 2020).…”
Section: Family Membermentioning
confidence: 99%
“…Sungai Tabuk District and Gambut District, located in Banjar Regency, are the two regions with extensive peatland and a potential for wildfires. The dangers of forest and peatland fires in these two areas make the lives of farmers more uncertain due to various challenges in the agricultural sector, ranging from climate, pests, diseases, and fluctuating prices (Ramadhan et al 2022). Their food security also becomes a unique issue to be studied, as most farmers practice subsistence farming, making their food security worth researching.…”
Section: Introductionmentioning
confidence: 99%
“…Village forest is one of the schemes of the Social Forestry policy to combat deforestation and degradation by involving the community in the management activities (Kumar 2015;Laksemi et al 2019). The motivation behind the policy was to promote community legal access to state forests (Ramadhan et al 2022) because it had led to unsustainable utilization of forest resources (Ragandhi et al 2021). As a reference, around 80% of forest areas in Meghalaya, the state of India, are owned and managed by indigenous institutions and the local community (Mir et al 2022).…”
Section: Introductionmentioning
confidence: 99%